Novel Biomarkers for Early Detection of Bacterial Meningitis: Penanda Biologis Baru untuk Deteksi Dini Meningitis Bakteri - Hommood, Ahmed Kadhim (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Bacterial meningitis is a life-threatening disease that demands rapid and accurate diagnosis to reduce morbidity and mortality. Specific Background: Conventional methods such as CSF culture, Gram staining, and biochemical tests often lack sensitivity, specificity, or require long processing time, limiting their usefulness in urgent clinical settings. Knowledge Gap: There remains limited evidence on the comparative diagnostic accuracy of novel biomarkers against routine laboratory parameters in early bacterial meningitis detection. Aims: This study aimed to evaluate the diagnostic value of Procalcitonin (PCT), Interleukin-6 (IL-6), and C-Reactive Protein (CRP) for early identification of bacterial meningitis compared to conventional laboratory markers. Results: Conducted as a case-control study in Iraq involving 100 patients and 50 controls, the findings showed significantly elevated serum levels of PCT, IL-6, and CRP in patients (p < 0.001). PCT demonstrated the highest diagnostic accuracy (AUC = 0.95), followed by IL-6 (0.93) and CRP (0.90), with all biomarkers correlating strongly with disease severity. Novelty: The study highlights PCT and IL-6 as highly reliable early diagnostic tools that surpass traditional parameters. Implications: Incorporating these biomarkers into diagnostic protocols can facilitate earlier interventions, improve monitoring, and reduce long-term complications in bacterial meningitis.Highlight : Procalcitonin has the strongest diagnostic value. IL-6 and CRP are reliable indicators of severity. Biomarkers support timely and accurate detection. Keywords : Bacterial Meningitis, Procalcitonin, Interleukin-6, C-Reactive Protein, Early Diagnosis